Food Coloring and Behavior - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
The association between the ingestion of tartrazine synthetic food coloring and behavioral change in children referred for assessment of hyperactivity was investigated at the Royal Children's Hospital, University of Melbourne, Australia.